Risk and Heterogeneity in Benefits from Vocational versus General Secondary Education: Estimates for Early and Mature Career Stages in Portugal - Joop Hartog; Pedro Raposo; Hugo Reis (Center for Economic Studies and ifo Institute (CESifo), 2023)
We estimate a dynamic model of individual labour market careers (turnover and search, wage development) on Portuguese panel data of graduates from vocational and general secondary education. We find that vocational graduates benefit more from the internal labour market than from the external market. This holds even more for mature than for young individuals. This hurts as among the mature, vocational has higher lay-off probability. To the common result that vocational education trades early employment advantage for later disadvantage we add a decomposition of employment status in its dynamic components. To the literature on wage effects we add a breakdown of variances in heterogeneity and risk.
Keywords: J30; J64; D80; I26; 330; risk; vocational education; search models